Creative Industry: Enhancing Competitive Advantage and Performance - Anjaningrum, Widiya Dewi; Rudamaga, Habel (Department of Management, Faculty of Economics and Business, Brawijaya University, 2019)
This study is a kind of field research which aims to find out how the relationship between market orientation, product creativity and innovation, competitive advantage and creative industry performance in Malang town, East Java, Indonesia. Data collection on 133 samples of creative entrepreneurs were carried out on a non-probability sampling through a questionnaire instrument. The data obtained were analyzed using Partial Least Square (PLS) analysis. The results of the study show that market orientation has a direct, positive and significant effect on product innovation, competitive advantage, and industry performance. The findings also state that there is an intervening effect of product innovation on the effect of market orientation on competitive advantage and industry performance, there is also an intervening effect on competitive advantage over the effect of market orientation on industry performance. Product creativity has a positive and significant effect on product innovation. However, there is not enough strong evidence to support the hypothesis that product creativity directly or indirectly affects competitive advantage through product innovation, as well as industry performance through competitive advantage. The intervening effect only occurs on the relationship of product creativity with product innovation and industry performance. The managerial implication of the study is that to achieve high industry performance, creative industries need to increase competitive advantage, especially through competitive pricing strategies, improving market orientation, and product innovation.